The Legal Implications for the Parties Involved in Autonomous Vehicle Transportation Contracts - Aqeel Karim , Researcher. Marwa; Ibrahim Al-Dhalami, Assist .Prof.Dr. Khalil (Basra studies journal, 2025)
This study examines the legal obligations arising for the parties to a transportation contract involving autonomous vehicles, highlighting the responsibilities borne by vehicle operators, manufacturers, and passengers. The study outlines the duties of vehicle operators in ensuring safety and providing continuous maintenance for autonomous vehicles, in addition to the necessity of receiving proper training and qualification to handle autonomous systems. It further investigates the manufacturers’ obligations to design vehicles safely and to regularly update the software to ensure optimal performance. Regarding passengers, the study clarifies their duty to follow the vehicle’s operating instructions and to report any malfunctions that may occur during the trip.